(untitled) (London Journal of Research In Science: Natural and Formal, 2024)
The foundation of this paper is the generation of all life by evolution. By this as- sumption, ‘everything’ has to be compatible with Darwin’s theory. I discuss some issues that concern animate beings. I ask some rhetorical questions. Answers are provided by speculations. I present arguments for an evolution and general thoughts. I show that some properties of animate beings are compatible with an evolution. The arguments except those in the chapter ‘Homosexuality’ are ideas of mine. All points only are personal views.